Study of the Completion of Follow-up After Helicobacter pylori Eradication Therapy - Yusaku Kajihara; Tadashi Shimoyama (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: Because no therapeutic regimens have an eradication rate of 100%, post-treatment evaluation is necessary to ensure that adequate eradication therapy for Helicobacter pylori has been provided. The fact that not all patients are evaluated after eradication therapy is a serious concern for both the medical care system and medical economy.Method: We performed a retrospective study of 411 patients who received first-line H. pylori eradication therapy at Fuyoukai Murakami Hospital from October 1, 2014 to March 31, 2016. We calculated the rate of post-treatment follow-up at 1 year after completing the eradication therapy. In addition, we excluded 76 patients who definitely received post-treatment evaluation because of follow-up appointments with gastroenterologists (n = 29) or return visits to other physicians (n = 47) and included 335 patients in the final study population. We used logistic regression models for identifying the relevant factors contributing to the completion of post-eradication follow-up.Results: The rate of completion of post-eradication follow-up was 78.8% (324/411). Multivariate analysis revealed that the adjusted odds ratios for age (≥ 48 years), gender (female) and preventive measures for gastric cancer (esophagogastroduodenoscopy after radiographic screening for gastric cancer and a desire to be examined for H. pylori infection) were 1.85 [95% confidence interval (CI): 1.11–3.09; p 0.05], 1.89 [95% CI: 1.07–3.34; p 0.05] and 4.01 [95% CI: 1.61–10.0; p 0.01], respectively.Conclusion: Age ≥ 48 years, female gender and preventive measures for gastric cancer were independently related to a higher rate of completion of post-eradication follow-up.